PENGARUH KADAR PEREKAT PHENOL FORMALDEHIDA TERHADAP KEAWETAN PAPAN PARTIKEL BAMBU ANDONG - Wa Ode Muliastuty Arsyad; Deazy Rachmi Trisatya (Jurnal Penelitian Hasil Hutan, 2020)
Bamboo is a very potential raw material for composite products. However, its susceptibility to moisture and organismsattack limits its utilization. This study examines the resistance of andong bamboo (Gigantochloa pseudoarundinacea(Steud.) Widjaja) particleboard against subterranean (Coptotermes curvignathus Holmgren) and dry-wood(Cryptotermes cynocephalus Light) termites attack. Particleboard with dimension of 35 cm x 35 cm x 1.5cm were manufactured from bamboo waste and it was glued with varying Phenol Formaldehyde (PF) content of 8%,10% and 12%. Specimens were tested according to the Indonesian standard (SNI 7207-2014). Results show thatvariation of PF content influence significantly into the weight loss of particleboard due to subterranean termite anddry-wood termite attacks. The differences of PF content also significantly influenced mortality of subterranean and drywood termites. Particleboard with 12% PF content had the lowest weight losses for subterranean termite (4.34%) anddry-wood termite (0.48%). Termite mortality was escalated with the increased PF content in particleboard. Bambooparticleboard with 12% PF content possessed highest termite mortalities of 71.5% and 76% for subterranean anddry-wood termites, respectively.